An experimental comparison of flat-panel detector performance for direct and indirect systems (initial experiences and physical evaluation) - Gomi T; Koshida K; Miyati T; Miyagawa J; Hirano H (Journal of Digital Imaging, 2006)
The purpose of this work was to compare direct and indirect detectors in terms of their system linearity, presampled modulation transfer function (MTF), Wiener spectrum (WS), noise equivalent quanta (NEQ), and power spectrum. Measurements were made on two flat-panel detectors, GE Revolution XR/d (indirect) and Shimadzu Safire (direct) radiographic techniques. The system linearity of the systems was measured using a time-scale method. The MTF of the systems was measured using an edge method. The WS of the systems was determined for a variable range of exposure levels by two-dimensional Fourier analysis. The NEQ was assessed from the measured MTF, WS, and estimated ideal signal-to-noise ratios. Power spectrum analyzed the chest phantom within artificial lesions. System linearity was excellent for the direct systems. For the direct system, the MTF was found to be significantly higher than that for the indirect systems. For the direct system, the WS was relatively uniform across all frequencies. In comparison, the indirect system exhibited a drop in the WS at high frequencies. At lower frequencies, the NEQ for the indirect system was noticeably higher than for the direct system. Power spectrum for the direct system was relatively flat and similar to that for white noise. The indirect system exhibited significant reduction at high spatial frequencies. In general, the direct systems exhibit improved image quality over indirect systems at comparable exposure dose.